The Implementation of the Constructivist Paradigm in the Curriculum Merdeka: Strategies, Challenges, and Its Implications for 21st-Century Education - Meri Andani; Tanti Permata Sari; Dian Lestari; Tri Muryanti; Sulastri Sulastri (Journal of Social Work and Science Education, 2026)
This study aims to explore the implementation of the constructivist paradigm within Indonesia’s Curriculum Merdeka and its implications for developing 21st-century competencies. Employing a Systematic Literature Review (SLR) methodology, it synthesizes empirical and theoretical studies from major academic databases. The results confirm that constructivist principles student autonomy, experiential learning, collaboration, and reflection effectively cultivate critical thinking, creativity, and problem-solving skills. A key novelty is the explicit alignment of these principles with the local educational philosophy of Ki Hajar Dewantara, framing constructivism as a realization of ‘freedom to learn’ and holistic character development. However, significant implementation barriers are identified, including gaps in teacher pedagogical understanding, insufficient digital literacy, and inadequate systemic support. The primary practical implication is the urgent need for comprehensive teacher professional development, reformed assessment systems, and policy-practice alignment to enable meaningful constructivist learning. This study contributes a synthesized scholarly perspective that bridges global constructivist theory with Indonesia’s specific curricular reform and cultural context, offering evidence-based guidance for sustainable educational transformation.